WORD CREATION BY PROSE V. TOKAREVA - Y N Kireeva; L I Plotnikova (Rusistika (Moskva. Online), 2017)
The article considers adjectival neologisms of V. Tokareva, through which the author verbalizes her attitude and aesthetic views. The paper presents a typology of such neologisms considering the ways of word formation and derivation formants. It is noted that the predominantly words, created according to productive word-formation models have clear meaning shown in their structure. The authors note that prefixes sub-, super- and suffixes -ovat-, -sk-, n- are the most productive ones. Among active prepositional formants are super-, semi-. The specific feature of V. Tokareva’s prose is the use of grammar forms. The article also identifies and analyzes structural, semantic, and functional features of neologisms. Special attention is drawn to the subjects and objects of reality receiving non-standard definitions.